Sports, storytelling and social media: a review and conceptualization. Issue 3 (23rd May 2018) - Laurell, Christofer; Söderman, Sten
Abstract : Purpose: Professional sports organizations have a long tradition of utilizing stories as part of their marketing efforts. However, as the media landscape has undergone considerable change as a result of information and communication technologies, most notably through social media, the conditions under which storytelling evolve have altered significantly. Therefore, the purpose of this paper is to explain how storytelling in the sports sector becomes integrated in social media. Design/methodology/approach: A conceptual review in three sequential steps is carried out. First, extant literature on the role and effects of storytelling is reviewed. This is followed by a review of the interplay between storytelling and the contemporary media landscape, with a particular focus on social media. Third, the authors link both literatures and, by doing so, illustrate the dynamic interplay of storytelling and social media in the sports sector. Findings: The conceptual review shows that storytelling can enact four sequential roles that are characterized by varying degrees of co-creation which, in relation to extant literature, has strong implications for the manageability of storytelling from the perspective of professional sports organizations. Originality/value: Based on the identified sequential roles that storytelling can enact in social media, this paper contributes to the field of sports marketing by depicting how the dynamics between storytelling and the social media landscape exhibit a shifting degree of manageability with regards to storytelling from the perspective of professional sports organizations.